2016
DOI: 10.1038/nplants.2016.164
|View full text |Cite
|
Sign up to set email alerts
|

T-DNA integration in plants results from polymerase-θ-mediated DNA repair

Abstract: Agrobacterium tumefaciens is a pathogenic bacterium, which transforms plants by transferring a discrete segment of its DNA, the T-DNA, to plant cells. The T-DNA then integrates into the plant genome. T-DNA biotechnology is widely exploited in the genetic engineering of model plants and crops. However, the molecular mechanism underlying T-DNA integration remains unknown. Here we demonstrate that in Arabidopsis thaliana T-DNA integration critically depends on polymerase theta (Pol θ). We find that TEBICHI/POLQ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 37 publications
4
137
1
Order By: Relevance
“…The ku80 and ku80 parp1 parp2 mutant lines appeared to have more templated-insertion events than wild-type and parp1 parp2 lines, although such insertions were found in all four genotypes (Table S3). Therefore, the templated insertions probably resulted from a KU80- and PARPs-independent alternative end-joining mechanism, such as that mediated by the recently discovered Pol θ (van Kregten et al 2016). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ku80 and ku80 parp1 parp2 mutant lines appeared to have more templated-insertion events than wild-type and parp1 parp2 lines, although such insertions were found in all four genotypes (Table S3). Therefore, the templated insertions probably resulted from a KU80- and PARPs-independent alternative end-joining mechanism, such as that mediated by the recently discovered Pol θ (van Kregten et al 2016). …”
Section: Resultsmentioning
confidence: 99%
“…In plants, templated insertions were also observed after DSB-induced repair in Arabidopsis and tobacco (Shirley et al 1992; Gorbunova and Levy 1997; Salomon and Puchta 1998; Lloyd et al 2012; Vu et al 2014). Furthermore, a recent study showed that the Arabidopsis Pol θ ortholog Tebichi ( Teb ) is essential for T-DNA integration (van Kregten et al 2016). Templated insertions were found at the repair junctions of T-DNA inserts, and it was shown that teb mutants were resistant to T-DNA integration and very sensitive to the DNA-damaging agents bleomycin and MMS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent breakthrough showed that T-DNA integration in A. thaliana requires the polymerase theta (Pol θ, At4g32700) (van Kregten et al, 2016). This discovery was inspired by the similar signature of doublestrand breaks (DSBs) of T-DNA integration with other systems.…”
Section: Integration Into the Plant Genome And Expression Of The T-dnamentioning
confidence: 99%
“…Based on the knowledge of molecular action of Pol θ, it has been proposed that T-DNA could target the random DSBs in the genome and the microhomology between the ends of T-DNA and the DSBs is required for the integration of T-DNA. Enhanced understanding of the mechanism of T-DNA integration may allow researchers to improve transgene targeting by introducing artificial breaks in the plant genome, which ideally will lead to specific integration of DNA fragments in a designated location (van Kregten et al, 2016).…”
Section: Integration Into the Plant Genome And Expression Of The T-dnamentioning
confidence: 99%
“…In addition, Pol θ plays a critical role in the generation of insertions during alternative end joining repair of collapsed replication forks in C . elegans [19, 20, 26] and during T-DNA insertion in Arabidopsis [27]. …”
Section: Introductionmentioning
confidence: 99%